Dissolution and mineralization behavior of metallic impurity content in diamond wire saw silicon powder during acid leaching. (1st March 2020) - Yang, Shicong; Wan, Xiaohan; Wei, Kuixian; Ma, Wenhui; Wang, Zhi
Abstract: Metallic impurity removal is essential for the recovery and purification of silicon from diamond wire saw silicon powder during acid leaching process. However, the related dissolution and mineralization behavior are unclear, which are the two main factors governing the capacity of metallic impurity removal during the acid leaching process for silicon recovery from diamond wire saw silicon powder. Metallic impurities have different characteristics in diamond wire saw silicon powder, especially the mineralization hindering the deep removal of impurities. In this study, the dissolution behavior in out-field and mixed lixiviant assisted intensification acid leaching were investigated, respectively. Further, it is of interest in this study to search the root cause of the dissolution behavior from impurity sources with a unique insight, where related theory was used to explain both the mineralization behavior and dissolution behavior. Results revealed that the acid leaching dissolution occurred from the surface inwards, as well as the root cause, which is caused by mineralization behavior. Owing to the fact that the bare silicon surface developed on the amorphous SiO2 layer, the retention of metallic impurity was the result of the SiO2 layer obstacle. The dissolution behavior could be explained as the disintegrating corrosion of SiO2 . For this reason, the 4 M HCl + 0.5 M HF mixture with a total removal efficiency of 99.28% outperformed out-field assisted leaching. This study can provide a suitable foundation for understanding the dissolution behavior and mineralization behavior for impurity removal, as well as contribute a roadmap for further silicon purification from diamond wire saw silicon powder. Graphical abstract: Image 1 Highlights: The out-field and mixed acid assisted intensification leaching were investigated. The homogeneous reaction kinetic model for impurities removal was validated. The dissolution and mineralization behavior of impurities in DWSSP were revealed. The results provides practical value for metallic impurities removal from DWSSP.